Public relations strategy of PT. Bank Central Asia in building corporate image through digital banking program - Kanti Permata,; Hamid, Farid (Technium Social Sciences Journal, 2020)
Challenges in the digital era have entered into various fields, including banking. The banking world, inevitably, has to adjust and transform to follow such developments. Public Relations plays an important role in educating the various parties who will be involved in this change. Public Relations is required to maintain the image and reputation of the institution it represents. The purpose of this research is to find out and analyze the strategy of public relations of PT. Bank Central Asia in building the corporate image through digital banking, using a qualitative research approach with a case study research method. Data collection techniques were conducted using in-depth interviews, observations, and relevant literature studies. The results show that PT Bank Central Asia is aware of the current era of technology disruption, and is moving to face dynamic changes and adapting to existing technological developments, in addition to also performing digital transformation. Public Relations strategies used through the use of digital banking to build an image include: a) research / data collection to determine the problems faced, then b) prepare a plan, c) implementation which includes promotion of digital banking and customer education, and d) evaluation to monitor the implementation that has been carried out whether it is in accordance with the objectives.